2020
DOI: 10.1248/cpb.c20-00041
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strategies for Targeted Brain Drug Delivery

Abstract: Because the brain is the most important human organ, many brain disorders can cause severe symptoms. For example, glioma, one type of brain tumor, is progressive and lethal, while neurodegenerative diseases cause severe disability. Nevertheless, medical treatment for brain diseases remains unsatisfactory, and therefore innovative therapies are desired. However, the development of therapies to treat some cerebral diseases is difficult because the blood-brain barrier (BBB) or blood-brain tumor barrier prevents d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 185 publications
0
7
0
Order By: Relevance
“…For instance, microbubbleassisted focused ultrasound (FUS) has shown potential in triggering temporary BBB opening and enabling systemic delivery of LNP/mRNA formulations to the brain with enhanced exogenous protein production across the BBB. [178,179]…”
Section: Accumulationmentioning
confidence: 99%
“…For instance, microbubbleassisted focused ultrasound (FUS) has shown potential in triggering temporary BBB opening and enabling systemic delivery of LNP/mRNA formulations to the brain with enhanced exogenous protein production across the BBB. [178,179]…”
Section: Accumulationmentioning
confidence: 99%
“…Therefore, the BBB has important biological significance for maintaining the basic stability of the internal environment of brain tissues and the normal physiological state of the CNS [385]. However, the presence of the BBB severely prevents most drugs such as many polyphenols from entering the brain to exert their effects [386]. Although a large number of studies have shown that some plant polyphenols can cross the BBB and reach the brain to exert a neuroprotective effect, there are still many polyphenols reported having indirect beneficial effects in neurodegenerative diseases [387][388][389].…”
Section: Indirect Beneficial Effect Of Plant Polyphenols On Neurodege...mentioning
confidence: 99%
“…Thus, in situ perfusion experiments provide in vivo evidence on possible transportability of peptides in intact form across the BBB. The criteria for the selection of BBB transporting peptides is (1) a dipeptide skeleton [because transporters related to influx transport direction recognize small nutrients such as glucose and amino acids (Ogawa et al 2020)], (2) PHT-1 substrate or dipeptides recognized by PHT1, which is abundantly expressed in the nerve system (Yamashita et al 1997), and (3) hydrophobicity that may assist the transcellular diffusive transport (Nau et al 1994). According to the criteria, the uptake (brain/perfusate ratio, μL/g-brain) of dipeptides listed in Table 2 is evaluated in in situ 2.0-min mouse perfusion experiments (Tanaka et al 2019).…”
Section: Blood-to-brain Transporting Peptidesmentioning
confidence: 99%
“…The BBB regulates or limits compounds acceptable for the brain, including amino acids, glucose, organic/inorganic compounds, and vitamins, whereas large compounds fail the BBB transport (Ogawa et al 2020). Thus, transporters capable of recognizing and transporting nutrients are individually expressed at luminal and abluminal sides of the BBB; typical influx (blood to brain direction) transporters are glucose transporter 1 (GLUT1) for glucose, large neutral amino acid transporter 1 (LAT1), and monocarboxylate transporter 1 (MCT1).…”
Section: Transport Route Of Bbb Transportable Peptidesmentioning
confidence: 99%